A pediatric structural MRI analysis of healthy brain development from newborns to young adults. Issue 12 (12th September 2017) - Levman, Jacob; MacDonald, Patrick; Lim, Ashley Ruyan; Forgeron, Cynthia; Takahashi, Emi
Abstract: Assessment of healthy brain maturation can be useful toward better understanding natural patterns of brain growth and toward the characterization of a variety of neurodevelopmental disorders as deviations from normal growth trajectories. Structural magnetic resonance imaging (MRI) provides excellent soft‐tissue contrast, which allows for the assessment of gray and white matter in the developing brain. We performed a large‐scale retrospective analysis of 993 pediatric structural brain MRI examinations of healthy subjects ( n  = 988, aged 0–32 years) imaged clinically at 3 T, and extracted a wide variety of measurements such as white matter volumes, cortical thickness, and gyral curvature localized to subregions of the brain. All extracted structural biomarkers were tested for their correlation with subject age at time of imaging, providing measurements that may assist in the assessment of neurological maturation. Additional analyses were also performed to assess gender‐based differences in the brain at a variety of developmental stages, and to assess hemispheric asymmetries. Results add to the literature by analyzing a realistic distribution of healthy participants imaged clinically, a useful cohort toward the investigation and creation of diagnostic tests for a variety of pathologies as aberrations from healthy growth trajectories. The next generation of diagnostic tests will be responsible for identifying pathological conditions from populations of healthy clinically imaged individuals. Hum Brain Mapp 38:5931–5942, 2017 . ©2017 Wiley Periodicals, Inc.